Representation of 1960s Masculinity in America through the Main Male Character in Elvis (2022) Film - Hidayanti, Nadia Rizkita (Universitas Airlangga, 2024)
This study examines the representation of masculinity in the mid-twentieth century in America as depicted by the main male character in the film Elvis (2022) by Baz Luhrmann. This study uses a descriptive qualitative method. The aims of this study are first to identify the characterization of the main male character in Elvis (2022) film and, secondly, to analyze and discuss the 1960s masculinity values in Elvis (2022) film. To reveal this, this study uses character and characterization theory by Petrie & Boggs and the concept of seven areas of masculinity by Janet Saltzman Chafetz. The results of this study reveal that the masculinity of the main male character describes seven areas of masculinity: 1) physical, 2) functional, 3) sexual aggressive, 4) emotional, 5) intelligence, 6) interpersonal, and 7) other personal characteristics. From the seven result areas found, it reveals that the main male character fulfills the masculine figure. Furthermore, it was found that the main male character in this film represents masculinity in the 1960s in America.